Resistive switching in Ag–TiO2 contacts - Ghenzi, Néstor (2012)
We study the electric pulse induced resistance switching of TiO2-Ag contacts at room temperature,exploring both unipolar and bipolar switching modes. Initially we observed unipolar response. After hundred pulsing cycles the unipolar switching response vanishes but the device can still be operated in bipolar switching regime. The underlying mechanism for resistance switching is modeled in terms of formation and rupture of filament, and movement of oxygen vacancies.